The Role Of Augmented Reality In Enhancing Students' Ability To Translate Scientific Thinking Into Effective Communication - Ellan Fatnoer Rachmawati; Hariyanto; Fauzan Adhim (INJECT (Interdisciplinary Journal of Communication), 2026)
Success depends not only on having brilliant ideas but also on how those ideas are conveyed. Effective communication is a fundamental prerequisite for success in human interaction. This research is motivated by the understanding that without good communication, all positive desires risk failing to be fully actualized. In the context of science learning, there are two keys to success: critical thinking skills to generate substantial ideas and social communication skills to disseminate them effectively. This research aims to develop Augmented Reality (AR)-based student worksheets (LKPD) to improve elementary school students' critical thinking and social communication skills in science learning. Using the ADDIE model of Research and Development (R&D) with a quasi-experimental design, the research instrument has been tested for validity and reliability. Independent t-test analysis shows a significant difference in achievement between the experimental and control groups, with an effect size (Cohen's d) in the large category. The results of the study are expected to demonstrate that integrating Augmented Reality into education not only sharpens students' logical thinking but also trains them to articulate complex ideas into easily understood messages, thereby balancing intellectual intelligence and social communication skills.